Przyjaźń i respekt. Wokół korespondencji Stanisława Pigonia i Romana Pollaka - Dopart, Bogusław (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
This sketch is based on the correspondence between Roman Pollak and Stanisław Pigoń between 1918 and 1968. The relationship between these two excellent literary historians, both students of the Jagiellonian University in the early 20th century, has both private and professional aspects. It also illustrates the fates of Polish scientists in the Second Polish Republic, during World War II and the occupation, and in the period of the so-called social realism. The ethics of friendship and the sense of creative fulfilment turned both scholars into friends devoid of jealousy and competition, content with each other’s successes and honestly congratulating each other on their achievements. The friendship between the professors from Cracow and Poznan was also based on respect to everything related to the university and academic calling. They both believed in the university that lasts and persistently fulfils its mission; both felt responsible for it and for the Polish studies in Poznan and Cracow. Finally, they exhibited strong attachment to the teaching profession. In the relationship between Pigoń and Pollak, one may find the realisation of a comprehensive and complete model of academic friendship which encompassed both the exchange of specific goods as well as personal satisfaction and the preservation of the highest personal and moral values.